Effects of plyometric training on physical fitness in team sport athletes: A systematic review - Slimani, M.; Chamari, K.; Miarka, B.; Del Vecchio, F. B.; Cheour, F. (Journal of Human Kinetics, 2016)
Plyometric training (PT) is a very popular form of physical conditioning of healthy individuals that has been extensively studied over the last decades. In this article, we critically review the available literature related to PT and its effects on physical fitness in team sport athletes. We also considered studies that combined PT with other popular training modalities (e.g. strength/sprint training). Generally, short-term PT (i.e. 2-3 sessions a week for 4-16 weeks) improves jump height, sprint and agility performances in team sport players. Literature shows that short PT (<8 weeks) has the potential to enhance a wide range of athletic performance (i.e. jumping, sprinting and agility) in children and young adult amateur players. Nevertheless, 6 to 7 weeks training appears to be too short to improve physical performance in elite male players. Available evidence suggests that short-term PT on non-rigid surfaces (i.e. aquatic, grass or sand-based PT) could elicit similar increases in jumping, sprinting and agility performances as traditional PT. Furthermore, the combination of various plyometric exercises and the bilateral and unilateral jumps could improve these performances more than the use of single plyometric drills or traditional PT. Thus, the present review shows a greater effect of PT alone on jump and sprint (30 m sprint performance only) performances than the combination of PT with sprint/strength training. Although many issues related to PT remain to be resolved, the results presented in this review allow recommending the use of well-designed and sport-specific PT as a safe and effective training modality for improving jumping and sprint performance as well as agility in team sport athletes.